Study on kinematic characteristics of the vertical-wheel on hybrid PDC bit - Qingliang Qi; Yingxin Yang; Yan Yang; Shiwei Niu; Xu Chen (Advances in Mechanical Engineering, 2022)
Aiming at improving the ROP of PDC bits in hard-to-drill formation, a new hybrid PDC bit with vertical-wheel is proposed in this paper, furtherly, the kinematic characteristics of the vertical-wheel are researched. Firstly, the coordinate system of the vertical-wheel is established, on basis of which the motion equation, the speed equation and the acceleration equation of the vertical-wheel is derived. Secondly, a series of unit rock-breaking experiments on the vertical-wheel with variable parameters are carried out, so that the average speed of vertical-wheel under different conditions is obtained and the theoretical model of average speed is established, furthermore, the influence of diameter and normal angle of the wheel on the average speed is analyzed. Thirdly, the speed of vertical-wheel under different conditions is measured on basis of the speed model with compensation coefficient, specifically, the calculated average speed of the Ø18 mm vertical-wheel according to the instantaneous speed model is 4.532 r/s, while the average speed obtained in experiment is 4.491 r/s, with an error of 0.9%, proving that the measuring method and modeling of the instantaneous speed are credible. Lastly, the theoretical conditions for continuous rotation of the wheel are obtained. The research results are of great significance to study the working mechanism of the vertical-wheel and provide technical support for the application of the hybrid PDC bit with vertical-wheels.